Sucrose utilization during somatic embryo development in black spruce: involvement of apoplastic invertase in the tissue and of extracellular invertase in the medium - Iraqi, Driss; Quy Le, Van; Lamhamedi, Mohammed S.; Tremblay, Francine M. (Journal of plant physiology, 2005)
The involvement of apoplastic invertase (Ap Inv) and sucrose synthase (SuSy) in the somatic embryo development of black spruce ( Picea mariana) was investigated under different maturation conditions. Replacing 6% sucrose with 3% or 1% sucrose in the maturation medium drastically decreased Ap Inv activity and amount in embryogenic tissues. This was accompanied by a decrease in the hexose pool that resulted in a lower starch deposition and protein amount in embryogenic tissues together with a lower embryo production. Conversely, SuSy activity was stable during maturation regardless of the sucrose concentration used in the medium. The presence of an extracellular enzyme responsible for sucrose hydrolysis in the maturation medium was also verified. An immunodetection experiment with anti-acid invertase antibodies revealed the presence of an active 53 kDa polypeptide in the medium, which had a similar molecular mass to that of the Ap Inv polypeptide found in embryogenic tissues. Utilization of sucrose from the medium by the tissues was also studied using labelled 14C-sucrose. Distribution of the radioactivity between tissular sucrose, glucose, and fructose showed that sucrose was diffused into the cell wall of embryogenic tissues and partly hydrolyzed by Ap Inv. These results show that the utilization of sucrose from the medium, the Ap Inv activity in embryogenic tissues, and the release of an active invertase into the medium operate together for the utilization of the carbohydrates during somatic embryo development in black spruce.